Preparation method of embedded manganese dioxide and zeolite composite material and application of embedded manganese dioxide and zeolite composite material in strontium ion adsorption

A one-pot synthesis method embeds MnO2 nanoparticles into zeolite using kaolinite, addressing nano-aggregation and pH sensitivity issues, resulting in a stable and efficient strontium ion adsorbent for seawater treatment.

CN119158539APending Publication Date: 2024-12-20HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411463830.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing manganese dioxide-based composite materials for strontium ion adsorption suffer from nano-aggregation, pH sensitivity, and instability in complex environments, with conventional synthesis methods being complex and inefficient.

Method used

A one-pot self-assembly reaction using kaolinite mineral, KMnO4, and MnSO4·H2O to embed MnO2 nanoparticles into a zeolite matrix, forming a stable and evenly distributed composite material through ionic bonding and spatial restriction.

Benefits of technology

The embedded composite material exhibits enhanced stability, adsorption capacity, and cost-effectiveness, effectively removing strontium ions from seawater with high interference, suitable for large-scale applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158539A_ABST
    Figure CN119158539A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of material preparation, and discloses a preparation method of an embedded manganese dioxide and zeolite composite material and application of the embedded manganese dioxide and zeolite composite material in strontium ion adsorption.The preparation method comprises the specific steps that 1, kaolinite raw ore is ground into fine powder, then high-temperature calcination is conducted, and metakaolin is obtained; step 2, preparing a KMnO4 solution and a MnSO4.H2O solution; the KMnO4 solution and the MnSO4.H2O solution are uniformly mixed, a NaOH solution is added, the pH value is adjusted, and a mixed solution is obtained; adding the metakaolin into the mixed solution, uniformly stirring, carrying out hydrothermal reaction, filtering, washing and drying to obtain the embedded manganese dioxide and zeolite composite material. Manganese dioxide is successfully embedded into a zeolite matrix to form a firm composite structure, and a new way is provided for solving the problem of Sr < 2 + > pollution in seawater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material preparation, and in particular to a preparation method of an embedded manganese dioxide@zeolite composite material and application of the same in strontium ion adsorption. Background Art

[0003] Separation of Sr from radioactive wastewater 2+ Among the various methods, adsorption is a promising method due to its simple operation, high efficiency and low secondary waste generation. Various adsorbents have been used to remove Sr 2+ , such as clay minerals, titanosilicates, layered metal sulfides and metal-organic frameworks (MOFs).

[0004] Among many adsorbents, zeolite has a large specific surface area, ordered pores, thermal stability, radiation resistance, and good Sr 2+ It has a special selectivity and has become a new method for adsorbing Sr in radioactive wastewater. 2+ Specifically, NaA molecular sieve has a structure based on [SiO4] 4- and [AlO4] 5- The complex three-dimensional crystalline aluminosilicate structure based on tetrahedral units has a porous network that facilitates ion exchange processes. + With Sr 2+ The ion exchange of zeolite is the 2+ However, zeolite has a high salinity and low Sr 2+ The application in seawater systems with high concentrations and large amounts of interfering ions is limited. Therefore, there is increasing interest in the synthesis of zeolite-based composites as a promising approach to overcome these limitations and improve their adsorption capacity.

[0005] Manganese dioxide (MnO2) has attracted widespread attention due to its low cost, good stability, high specific surface area, structural flexibility, efficient oxidation performance, and efficient adsorption of many heavy metals. However, manganese dioxide has some inherent disadvantages. First, it is prone to nano-aggregation, which will cause it to be + Secondly, it is sensitive to pH, especially when the pH value is below 5, its adsorption capacity is almost negligible. In view of this, it has become a top priority to study a simpler and more effective manganese dioxide composite material.

[0006] At present, the synthesis of manganese dioxide / zeolite composite materials is usually carried out by a step-by-step method. Although the ratio of manganese dioxide and zeolite can be controlled by step-by-step synthesis, the performance of the composite material is improved to a certain extent. However, its disadvantages are also obvious. First, the step-by-step synthesis process is relatively complicated, involving multi-step reactions and operations, which increases time and cost; secondly, because it is carried out step by step, the generated manganese dioxide covers the surface of the zeolite to form a coating structure, which affects the full performance of the composite material: on the one hand, this coating structure blocks the originally rich pores of the zeolite to a certain extent, reduces the porosity of the zeolite, and thus affects its adsorption capacity for substances; on the other hand, although the coating structure combines the characteristics of manganese dioxide and zeolite to a certain extent, this combination is relatively loose. In practical applications, when faced with complex environmental conditions, such as water flow impact, pH changes, etc., manganese dioxide is prone to fall off the surface of the zeolite, thereby reducing the stability and durability of the composite material and limiting its wide application in practical engineering. Summary of the invention

[0007] Purpose of the invention: In view of the problems existing in the prior art, the present invention provides a method for preparing an embedded manganese dioxide @ zeolite composite material and its application in strontium ion adsorption. The embedded manganese dioxide @ zeolite composite material is synthesized by a one-pot self-assembly reaction using low-cost kaolinite mineral, KMnO4 and MnSO4·H2O as raw materials. The present invention successfully embeds MnO2 nanoparticles into the zeolite molecular sieve matrix. This new composite material shows great potential in adsorbing strontium ions, which is a promising method for removing Sr from complex seawater. 2+ This paper provides a feasible and cost-effective strategy to solve the problem of Sr 2+ Pollution issues offer new avenues.

[0008] Technical solution: On the one hand, the present invention provides a method for preparing an embedded manganese dioxide@zeolite composite material, comprising the following steps: Step 1: Grind the kaolinite ore into fine powder, and then calcine at high temperature to obtain metakaolin; Step 2, prepare KMnO4 solution and MnSO4·H2O solution; mix the KMnO4 solution and the MnSO4·H2O solution evenly, add NaOH solution, adjust the pH value, then add the metakaolin, stir evenly to obtain a mixed solution; hydrothermal reaction, filter, wash, and dry to obtain an embedded manganese dioxide@zeolite composite material.

[0009] Furthermore, in step 1, the specific conditions of the high temperature calcination are: the calcination temperature is 600-900 o C, calcination time is 1-3 h.

[0010] Further, in step 2, the concentration of the KMnO4 solution is 0.089-0.095 mol / L; In step 2, the concentration of the MnSO4·H2O solution is 0.125-0.145 mol / L.

[0011] Furthermore, in step 2, in the mixed solution, the mass ratio of metakaolin, KMnO4 and MnSO4·H2O is 5:0.5-4:1-6.

[0012] Furthermore, in step 2, NaOH solution is added to adjust the pH value to 6-7.

[0013] Preferably, in step 2, the stirring time is 30-60 min.

[0014] Furthermore, in step 2, the specific conditions of the hydrothermal reaction are: the reaction temperature is 80-120 o C, reaction time is 3-5 h.

[0015] Furthermore, in step 2, the specific step of washing is: washing with distilled water for more than 3 times to reduce the pH value of the embedded manganese dioxide@zeolite composite material to 6-8.

[0016] Preferably, in step 2, the specific conditions for drying are: drying temperature is 100-150 o C; drying time is 6-12 h.

[0017] On the other hand, the present invention provides an application of an embedded manganese dioxide@zeolite composite material prepared by any of the methods described above in strontium ion adsorption.

[0018] Synthesis principle: The three-dimensional framework structure of zeolite has abundant pores and channels. When the size of these pores and channels matches the size of manganese dioxide nanoparticles, manganese dioxide particles can easily enter the pores of zeolite. In addition, the structure of zeolite has certain rigidity and stability, which can maintain the integrity of the structure after manganese dioxide is embedded, thus forming an embedded structure. In addition, when manganese dioxide is generated in the pores of zeolite, the growth and aggregation of manganese dioxide are inhibited by the limitation of the pore space of zeolite, thus forming an embedded structure with good dispersion. This spatial restriction effect enables manganese dioxide to be evenly distributed in the pores of zeolite, improving the stability and performance of the composite material. Finally, during the synthesis process, ionic bonds may be formed between manganese ions and oxygen atoms or other anions on the surface of zeolite. Manganese ions have a high charge density and are easily attracted to negatively charged groups on the surface of zeolite to form ionic bonds. The formation of this ionic bond helps to firmly bind manganese dioxide to the surface and pores of zeolite.

[0019] Beneficial effects: The specific beneficial effects of the present invention are as follows: 1. Simple synthesis method: The present invention adopts a one-pot self-assembly reaction to prepare an embedded manganese dioxide @ zeolite composite material. The synthesis technology is simple and efficient, which reduces complex operation steps and avoids the need for multiple treatments and purification, thereby improving the yield and efficiency. This synthesis technology makes the reaction process more controllable, reduces the loss of intermediate products and the introduction of impurities. In practical applications, it not only saves time and cost, but also provides the possibility for large-scale application.

[0020] 2. Stable structure: The present invention adopts a one-pot self-assembly reaction to prepare an embedded manganese dioxide @ zeolite composite material. Through the hydrothermal reaction of co-crystallization, MnO2 is generated simultaneously when zeolite (Z4A) is generated. Its unique synthesis method promotes the close combination of the two. In terms of microstructure, manganese dioxide is successfully embedded in the zeolite matrix to form a strong composite structure. On the one hand, the porosity of Z4A is well preserved, and on the other hand, the adsorption performance of the material is significantly improved. The embedded manganese dioxide @ zeolite composite material prepared by the present invention shows excellent stability in practical applications and can withstand the test of different environments, such as temperature changes, pH changes, etc. In adsorption applications, its stable structure ensures efficient adsorption performance, which is a solution to effectively separate Sr from seawater systems with complex components. 2+ Provides reliable material selection.

[0021] 3. Performance improvement: The embedded structure can increase the dispersion of manganese dioxide in zeolite, allowing manganese dioxide to be more evenly distributed in the pores and surface of the zeolite, thereby increasing the contact area with the target substance. This high dispersibility and large contact area help improve the composite material's adsorption capacity for the target substance. For example, when treating wastewater containing heavy metal ions, the embedded composite material can adsorb heavy metal ions more quickly and thoroughly, improving the purification effect of the wastewater. However, the distribution of manganese dioxide in conventional composite materials may not be uniform enough, and there is agglomeration, which causes the manganese dioxide in some areas to be unable to fully exert its adsorption effect, reducing the overall adsorption performance.

[0022] 4. Cost-effectiveness: The present invention directly uses low-cost and widely available kaolinite mineral as raw material, which makes the cost of the entire synthesis process relatively low and more conducive to large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 For 4A zeolite ( Figure 1 a. Figure 1 b) and the embedded manganese dioxide@zeolite composite material prepared by the present invention ( Figure 1 c. Figure 1 d) SEM image; Figure 2For Sr 2+ Langmuir fitting isotherms on conventional MnO2, 4A zeolite, MnO2@Z4A-8, MnO2@Z4A-9, MnO2@Z4A-13, and MnO2@Z4A-30 adsorbents; Figure 3 The adsorption of Sr in seawater by 4A zeolite and MnO2@Z4A-9 at different adsorbent dosages 2+ The adsorption rate (Na + =10,000mg / L, K + =400 mg / L, Mg 2+ =12,000 mg / L, Ca 2+ =400 mg / L); Figure 4 This is the SEM image of a conventional manganese dioxide@zeolite composite material. DETAILED DESCRIPTION

[0024] The present invention is described in detail below in conjunction with the embodiments.

[0025] Implementation 1: This embodiment provides a method for preparing an embedded manganese dioxide@zeolite composite material and its application in strontium ion adsorption, as follows: First, the raw kaolinite was ground into powder and then transferred to a tube furnace and calcined at 800°C for 2 h in an air atmosphere to obtain metakaolin. Secondly, 0.727 g KMnO4 and 1.166 g MnSO4·H2O were dissolved in deionized water, and the pH value of the solution was adjusted to 6-7. Subsequently, 5 g metakaolin and 6.868 g NaOH were added to the mixture. After thorough mixing, the mixture was transferred to a polytetrafluoroethylene-lined autoclave, and then the autoclave was transferred to an electric constant temperature blast drying oven for hydrothermal reaction at 90 °C for 4 h. Finally, the hydrothermal reaction product was filtered and washed using a desktop circulating water multi-purpose vacuum pump until the eluent was neutral to remove any intermediates and unreacted chemicals. Finally, the obtained sample was dried at 100 °C for 24 h to obtain an embedded manganese dioxide@zeolite composite material, recorded as MnO2@Z4As-9.

[0026] A glass bottle containing a certain amount of MnO2@Z4As-9 adsorbent and 10 ml of the adsorbed solution was fixed in a water bath constant temperature shaker at 25 o C constant temperature conditions. After the experiment, the solution was filtered and the Sr in the solution was detected by ICP-OES. 2+ concentration.

[0027] Implementation 2: This embodiment provides a method for preparing an embedded manganese dioxide@zeolite composite material and its application in strontium ion adsorption, as follows: First, the raw kaolinite was ground into powder and then transferred to a tube furnace and calcined at 800°C for 2 h in an air atmosphere to obtain metakaolin. Secondly, 0.908 g KMnO4 and 1.458 g MnSO4·H2O were dissolved in deionized water, and the pH value of the solution was adjusted to 6-7. Subsequently, 5 g metakaolin and 6.960 g NaOH were added to the mixture. After thorough mixing, the mixture was transferred to a polytetrafluoroethylene-lined autoclave, and then the autoclave was transferred to an electric constant temperature blast drying oven for hydrothermal reaction at 90 °C for 4 h. Finally, the hydrothermal reaction product was filtered and washed using a desktop circulating water multi-purpose vacuum pump until the eluent was neutral to remove any intermediates and unreacted chemicals. Finally, the obtained sample was dried at 100 °C for 24 h to obtain an embedded manganese dioxide@zeolite composite material, recorded as MnO2@Z4As-13.

[0028] A glass bottle containing a certain amount of MnO2@Z4As-13 adsorbent and 10 ml of the adsorbed solution was fixed in a water bath constant temperature shaker at 25 o C constant temperature conditions. After the experiment, the solution was filtered and the Sr in the solution was detected by ICP-OES. 2+ concentration.

[0029] Implementation 3: This embodiment is substantially the same as Embodiment 1, except that the amounts of NaOH, KMnO4 and MnSO4·H2O added in this embodiment are 6.5 g, 3.6356 g and 5.8323 g, respectively. The embedded manganese dioxide@zeolite composite material prepared in this embodiment is recorded as MnO2@Z4As-30.

[0030] Apart from this, this embodiment is completely the same as Embodiment 1 and will not be described in detail here.

[0031] Comparative Example: Synthesis of conventional manganese dioxide@zeolite composites The synthesis of conventional manganese dioxide@zeolite composite materials adopts a step-by-step synthesis method.

[0032] First, 6.5 g of sodium hydroxide was dissolved in 50 ml of deionized water, stirred evenly and clear, and then 5 g of metakaolin was added to the sodium hydroxide solution, mixed evenly, stirred at room temperature for 30 min, and the mixture was transferred to a high-pressure reactor, and then the high-pressure reactor was transferred to an electric constant temperature blast drying oven for hydrothermal reaction at 90 °C for 4 h. Finally, the hydrothermal reaction product was filtered and washed using a desktop circulating water multi-purpose vacuum pump until the eluent was neutral to remove any intermediates and unreacted chemicals. Finally, the obtained sample was dried at 100 °C for 24 h.

[0033] Secondly, 0.727 g KMnO4 and 1.166 g MnSO4·H2O were dissolved in deionized water, and the pH value of the solution was adjusted to 6-7. After thorough mixing, the mixture was transferred to a polytetrafluoroethylene-lined autoclave, and then the autoclave was transferred to an electric constant temperature blast drying oven for reaction at 90 °C for 4 h. Finally, the reaction product was filtered and washed using a desktop circulating water multi-purpose vacuum pump until the eluent was neutral to remove any intermediates and unreacted chemicals.

[0034] Finally, the synthesized manganese dioxide and zeolite are physically mixed to obtain a conventional manganese dioxide@zeolite composite material.

[0035] By comparing the conventional manganese dioxide@zeolite composites ( Figure 4 ) and embedded manganese dioxide@zeolite composites ( Figure 1), we can find that: in conventional composite materials, it can be seen from the scanning electron microscope that the manganese dioxide particles are unevenly distributed on the surface of the zeolite, and there is obvious agglomeration. The manganese dioxide particles are relatively independently attached to the outer surface of the zeolite, and the combination with the zeolite is relatively loose, with no obvious signs of embedding, showing a state similar to "wrapping" or "attachment". For embedded composite materials, from the scanning electron microscope, the manganese dioxide particles are obviously embedded in the internal structure of the zeolite. Manganese dioxide is in a "mosaic" state inside the zeolite, and part of the manganese dioxide penetrates into the deep structure of the zeolite, and the combination with the zeolite is tighter, forming a mutually nested structure. In conventional composite materials, manganese dioxide is mainly distributed on the surface of the zeolite. Although it can also increase the adsorption sites of the material, its available adsorption area is relatively small. Therefore, the adsorption capacity of conventional composite materials may be improved to a certain extent, but the increase is relatively limited. The embedded structure makes the combination of manganese dioxide and zeolite closer, increases the specific surface area and porosity of the material, and provides more adsorption sites. At the same time, the embedding of manganese dioxide into the zeolite can also change the internal structure of the zeolite, thereby enhancing its adsorption capacity for adsorbates. In addition, by fitting the Langmuir solid-liquid adsorption isotherm model, we found that the conventional manganese dioxide@zeolite composite material has a strong adsorption capacity for Sr 2+ The adsorption capacity of embedded manganese dioxide@zeolite composite material was 120.51 mg / g under the same experimental conditions. 2+ The adsorption capacity of Sr 2+ In terms of adsorption capacity, the embedded composite material showed more outstanding performance and had a higher adsorption capacity.

[0036] Characterization and performance analysis of the embedded manganese dioxide@zeolite composite material prepared by the present invention: Figure 1 For 4A zeolite ( Figure 1 a. Figure 1 b) and the embedded manganese dioxide@zeolite composite material prepared by the present invention ( Figure 1 c. Figure 1 d) SEM image, we can clearly see that manganese dioxide is successfully embedded in the zeolite matrix.

[0037] Figure 2 Sr 2+From the Langmuir fitting isotherms on conventional MnO2, 4A zeolite, MnO2@Z4A-8, MnO2@Z4A-9, MnO2@Z4A-13 and MnO2@Z4A-30 adsorbents, we can clearly see that the adsorption capacity of MnO2@Z4A-9 adsorbent material can reach 177.49 mg / g, which is 39.96% higher than that of Z4A alone, exceeding most of the adsorption capacity of Sr 2+ adsorption material.

[0038] Figure 3 The adsorption of Sr in seawater by 4A zeolite and MnO2@Z4A-9 at different adsorbent dosages 2+ The adsorption rate (Na + =10,000mg / L, K + =400 mg / L, Mg 2+ =12,000 mg / L, Ca 2+ =400 mg / L), we found that when the dosage increased to 10 g / L, the removal rates of Sr by MnO2@Z4A-9 and Z4A reached 98.4% and 87.5%, respectively. This shows that even in the presence of Ca 2+ In real seawater with high concentration, increasing the amount of adsorbent can still effectively remove Sr 2+ In addition, in the seawater system, MnO2@Z4A-9 has a strong 2+ The adsorption capacity of Z4A is significantly better than that of Z4A. These results show that the embedded manganese dioxide@zeolite composite material prepared by the present invention has great potential in adsorbing strontium ions, which is a promising method for removing Sr from complex seawater. 2+ This paper provides a feasible and cost-effective strategy to solve the problem of Sr 2+ Pollution problem provides a new approach and has good application prospects in radioactively contaminated seawater systems.

[0039] Figure 4 This is a SEM image of a conventional manganese dioxide @ zeolite composite material. We can clearly see that the manganese dioxide particles are unevenly distributed on the zeolite surface and there is obvious agglomeration. The manganese dioxide particles are relatively independently attached to the outer surface of the zeolite, and the bond between them and the zeolite is relatively loose, with no obvious signs of embedding, showing a state similar to "wrapping" or "attachment".

[0040] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent transformation or modification made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an embedded manganese dioxide@zeolite composite material, characterized in that: The following steps are involved: Step 1: Grind the kaolinite ore into fine powder, and then calcine at high temperature to obtain metakaolin; Step 2, prepare KMnO4 solution and MnSO4·H2O solution; mix the KMnO4 solution and the MnSO4·H2O solution evenly, add NaOH solution, adjust the pH value, then add the metakaolin, stir evenly to obtain a mixed solution; hydrothermal reaction, filter, wash, and dry to obtain an embedded manganese dioxide@zeolite composite material.

2. The method for preparing the embedded manganese dioxide@zeolite composite material according to claim 1, characterized in that: In step 1, the specific conditions of the high temperature calcination are: the calcination temperature is 600-900 o C, calcination time is 1-3 h.

3. The method for preparing the embedded manganese dioxide@zeolite composite material according to claim 1, characterized in that: In step 2, the concentration of the KMnO4 solution is 0.089-0.095 mol / L; In step 2, the concentration of the MnSO4·H2O solution is 0.125-0.145 mol / L.

4. The method for preparing the embedded manganese dioxide@zeolite composite material according to claim 1, characterized in that: In step 2, in the mixed solution, the mass ratio of metakaolin, KMnO4 and MnSO4·H2O is 5:0.5-4:1-6.

5. The method for preparing the embedded manganese dioxide@zeolite composite material according to claim 1, characterized in that: In step 2, NaOH solution is added to adjust the pH value to 6-7.

6. The method for preparing the embedded manganese dioxide@zeolite composite material according to claim 1, characterized in that: In step 2, the stirring time is 30-60 min.

7. The method for preparing the embedded manganese dioxide@zeolite composite material according to claim 1, characterized in that: In step 2, the specific conditions of the hydrothermal reaction are: the reaction temperature is 80-120 o C, reaction time is 3-5 h.

8. The method for preparing the embedded manganese dioxide@zeolite composite material according to claim 1, characterized in that: In step 2, the specific steps of washing are: washing with distilled water for more than 3 times to reduce the pH value of the embedded manganese dioxide@zeolite composite material to 6-8.

9. The method for preparing the embedded manganese dioxide@zeolite composite material according to claim 1, characterized in that: In step 2, the specific conditions for drying are: drying temperature is 100-150 o C; drying time is 6-12 h.

10. Use of the embedded manganese dioxide@zeolite composite material prepared by the method according to any one of claims 1 to 9 in strontium ion adsorption.